Shoulder dystocia: impacts, prevention, prognosis, troubleshooting - G. Kontopoulos (Epistīmonika Chronika, 2017)
Shoulder dystocia is one of the most dramatic complications encountered in obstetrics. When this complication occurs, it can result in increased maternal morbidity rate and increased incidence of neonatal morbidity and mortality. Although several risk factors are clearly associated with dystocia shoulder. The recognition of individual cases of shoulder dystocia has proven impossible in practice, before they occur during labor. Several guidelines have been published concerning the treatment of shoulder dystocia, aiming to instruct obstetricians to a maneuver sequence to reduce maternal and neonatal morbidity and mortality.